Cross-region migration of brides and gender relations in a daughter deficit context. (2nd January 2017) - Srinivasan, Sharada
Abstract : In recent years there is a growing interest in the phenomenon of across-region marriages and the wellbeing of women in such marriages in female deficit regions in countries such as India and China. Several men in district Namakkal in the south Indian state of Tamil Nadu which has had a long history of daughter elimination are currently experiencing a delay in marriage due to female deficit, educational and occupational incompatibility, and women's changing marriage preferences, with many bringing brides from outside the region. Women who are priced out of the marriage market in Kerala, a state where women occupy a relatively better status, are also marrying these men. Based on ethnographic fieldwork, this paper argues that the experiences of cross-region brides are not idiosyncratic or ad hoc but are shaped by and embedded within the intersection of caste, class, gender and kinship. In particular the gender contexts in both the place of origin and the place women are married into, affect their wellbeing. While such unions have the potential to create a win-win situation for both parties and challenge practices such as caste endogamy and dowry, they also reinforce unequal gender norms that maintain male privilege.